A Recommendation for New Diction Rhymes to be used in Turkish Diction Education Studies - COBAN, Ismail (Asian Journal of Education and Training, 2020)
Acquisition of the ability to speak correctly and effectively is one of the main purposes of elocution. One of the conditions required to achieve this is to have a good diction. Although the students speak standard Turkish language at schools, they have poor diction due to being under the influence of local dialects in the family and outside the school. This affects the process of making the students acquire the ability of speaking, one of the main objectives of Turkish teaching. The aim of the study addressed with case study method is to determine how the diction rhymes should be to be prepared by the prospective Turkish teachers in order to correct and improve the diction of the students. The study group constituted 46 first-grade prospective Turkish teachers studying in the Department of Turkish Language Education, in Ataturk University between 2017-2018 academic year. Prospective Turkish teachers were asked to create a diction rhyme for 10 sounds “b, p, d, t, g, k, e, o, u, ü”. 434 diction rhymes were obtained as a result of the research. Rhymes were examined in terms of length, including the number of the target sound, entertainment, creativity, and availability in diction training. As a result of the examination, 149 of the recommended rhymes were determined to have the capability to be used in diction training.